Sub-tenon Anaesthesia versus Intracameral Anaesthesia in Patients Undergoing cataract extraction: A Comparative Study of the Level of Pain, Visual Perception and Anxiety - Mushawiahti Mustapha; Muhammad Hazzril Hamzah; Soon Ken Chow; Nur Syuhada Zulkifli; Zalikha Abdul Latiff; Diana Melissa Dualim; Su Gaik Cheah; Mae Lynn Catherine Bastion (University Library System, University of Pittsburgh, 2014)
Background: Phacoemulsification is a modern method of cataract extraction. Sub-tenon anaesthesia used to be the preferred anaesthetic technique for this procedure before intracameral anaesthesia gained its popularity in recent years. Nevertheless, many surgeons still believe that sub-tenon anaesthesia is better than topical anaesthesia. This study aimed to evaluate and compare the experiences of patients who were treated for cataract by phacoemulsification surgery using either sub-tenon or intracameral anaesthesia. Methods: Cross-sectional study conducted at Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur, Malaysia. Participants were asked to complete a questionnaire within 1-2 hours following surgery. The questionnaires were designed to gather information on the patient's level of anxiety, visual perception and amount of pain experienced during cataract surgery. Results: A total of 62 patients were included in the study. Thirty-one patients received anaesthesia by sub-tenon injection, whereas another 31 patients received anaesthesia by intracameral injection. There were no significant differences in the level of pain experienced by the two groups of patients during instillation of anaesthesia and during surgery (p=0.205 and p=0.592, respectively). There were also no significant differences in terms of visual perception and anxiety levels during surgery between the two groups (p=0.178 and p=0.731, respectively). Conclusion: Intracameral anaesthesia obviates the need for an injection during cataract surgery and is as comfortable for patients as sub-tenon anaesthesia in terms of visual perception, level of pain, and anxiety.